Mechanobiological Strategies to Enhance Stem Cell Functionality for Regenerative Medicine and Tissue Engineering - Shafiq, Muhammad; Ali, Onaza; Han, Seong-Beom; Kim, Dong-Hwee (Frontiers in Cell and Developmental Biology, 2021)
Stem cells have been extensively used in regenerative medicine and tissue engineering; however, they often lose their functionality because of the inflammatory microenvironment. This leads to their poor survival, retention, and engraftment at transplantation sites. Considering the rapid loss of transplanted cells due to poor cell-cell and cell-extracellular matrix (ECM) interactions during transplantation, it has been reasoned that stem cells mainly mediate reparative responses via paracrine mechanisms, including the secretion of extracellular vesicles (EVs). Ameliorating poor cell-cell and cell-ECM interactions may obviate the limitations associated with the poor retention and engraftment of transplanted cells and enable them to mediate tissue repair through the sustained and localized presentation of secreted bioactive cues. Biomaterial-mediated strategies may be leveraged to confer stem cells enhanced immunomodulatory properties, as well as better engraftment and retention at the target site. In these approaches, biomaterials have been exploited to spatiotemporally present bioactive cues to stem cell-laden platforms (e.g., aggregates, microtissues, and tissue-engineered constructs). An array of biomaterials, such as nanoparticles, hydrogels, and scaffolds, has been exploited to facilitate stem cells function at the target site. Additionally, biomaterials can be harnessed to suppress the inflammatory microenvironment to induce enhanced tissue repair. In this review, we summarize biomaterial-based platforms that impact stem cell function for better tissue repair that may have broader implications for the treatment of various diseases as well as tissue regeneration.